Expression of Fc-Gamma Receptors of Neutrophils in Preterm Infants of Different Gestational Age - Vladimir E. Mukhin; Daria A. Praulova; Lyudmila L. Pankratyeva; Olga I. Mileva; Alexander G. Rumyantsev; Nikolay N. Volodin ("Paediatrician" Publishers LLC, 2016)
Background: Premature infants have a high risk of bacterial infections facilitated by the immaturity of their immune system.Objective: Our aim was to study the expression of Fc-gamma receptors of neutrophils and the possibility of its modulation in preterm infants (with a low, LBW, very low, VLBW and extremely low, ELBW, birth weight) with bacterial infection.Methods: We examined cord blood samples, as well as peripheral venous blood samples of newborns taken at 28-30th day of life. The flow cytofluorometry method was used to determine the level of surface expression of Fc-gamma receptors by neutrophils (CD64, CD32, CD16), phagocytic activity and oxygen burst of granulocytes stimulated with fluorescently labelled Escherichia coli. Results: We examined blood samples of 10 full-term infants, 20 preterm infants with LBW, 18 preterm infants with VLBW and ELBW. CD64 expression in preterm infants at birth was higher than in full-term children and made 6.0 (5.3; 9.8), 7.1 (5.1; 11.5), and 4.27 (2.4; 5.8) MFI respectively (p = 0.013). CD16 expression in preterm infants, in contrast, was lower: 99.7 (71.3; 126.0) and 80.9 (58.7; 114.8), and 125.3 (95.5; 144.1) MFI respectively (p = 0.021). By the end of the 1st month of life, CD16 expression of peripheral blood neutrophils in preterm infants increased to 126.6 (110.1; 129.0) MFI in children with LBW and to 118.5 (99.5; 132.2) MFI - in children with VLBW/ELBW. CD32 expression in compared groups did not differ. A correlation between the intensity of the oxygen burst of neutrophils and gestational age was established (r = 0.67; p <0.001). Neutrophil culture of preterm infants in the presence of granulocyte colony stimulating factor (G-CSF) results in a 2.4-5-fold increase in CD16, CD32 expression and enhancement of oxygen burst.Conclusion: Preterm infants are characterized by deregulated expression of Fc-gamma receptors and functional impairment of neutrophils. G-CSF modulates the expression of CD16 and CD32 on the surface of neutrophils and enhances the oxygen burst in them.